Spearman Rank Correlation Analysis to Assess Satisfaction with Study Locations at Tadika CERIA - Octavia, Annisa Suci; Utomo, Fandy Setyo (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
One of the activities that is routinely held during the learning process is filling out questionnaires by parents to determine the quality of Tadika CERIA education and services. The results of this questionnaire were then analyzed using the Spearman Rank Correlation method. This study aims to apply correlation analysis using Python to evaluate student satisfaction with the learning location at Tadika CERIA. Utilizing a dataset of survey responses that includes variables such as cleanliness, quality of teaching, and communication, analysis was conducted to identify key factors influencing student satisfaction. This approach not only shows the practical application of Python in data processing and statistical analysis, but also provides valuable insights for school administrators in improving the quality of the learning environment. The results show a positive correlation between certain aspects and student satisfaction, underscoring the importance of a deep understanding of student preferences and needs in the development of a conducive learning environment. This research makes an important contribution in the context of early childhood education, offering a foundation for further research in an effort to improve the holistic educational experience.